Motives of labour migrations of foreign elite athletes to Polish table tennis clubs - Lenartowicz, M.; Ciok, A. (Physical Culture and Sport. Studies and Research, 2021)
The paper presents results of empirical study on elite foreign athletes working in Polish top table tennis clubs. It focuses on professional migration motives of elite table tennis players. In-depth interviews were carried out with 27 foreign table tennis players from 10 countries, who were playing for two top league clubs in Poland, and with 8 club coaches who were working with foreign players. Research was conducted during the 2014/2015 league season. The surveyed athletes came both from European countries of higher economic status than Poland and from outside Europe, from countries of lower economic status. A significant number of the surveyed players (11) arrived at Poland from China. The reasons why the surveyed players decided to come to Poland were varied and included both pull factors resulting from attractiveness of work abroad and factors pushing the players away from their home country sport system. Among the motives mentioned by the respondents, the major ones seem to be the desire to continue their professional career and to develop as players. Most of the respondents reported a few factors motivating them to come to Poland and play in the Polish table tennis league. Most often they gave several reasons altogether and it is not easy to classify them as exclusively one of the typo- logies of sport migrants presented in the literature. For some of the respondents, the decisive criterion was the high level of the Polish table tennis league, staying only slightly behind the French and German leagues. For others, good financial conditions offered by the Polish clubs and the possibility of improving living conditions were of key importance. Push factors were particularly important in the case of Asian players representing a very high level of sport skills, however slightly lower than the level of the Chinese national team.